Biochemical and endocrine aspects of oxytocin production by the mammalian corpus luteum - Stormshak, Fredrick (BioMed Central, 2003)
A review of the current state of knowledge of oxytocin production by the preovulatory follicle and corpus luteum is presented. Corpora lutea of a number of mammalian species have been found to synthesize oxytocin. However, the synthesis and secretion of this nanopeptide by the corpus luteum of the ruminant has been most extensively studied because of the potential role of this peptide in facilitating luteal regression. While much information exists relative to various biochemical and endocrine factors that impact on oxytocin gene expression, this aspect about luteal synthesis of this peptide hormone remains enigmatic. Prostaglandin F-2α (PGF-2α) has been shown to be a primary endogenous hormone responsible for triggering luteal secretion of oxytocin. Details are provided regarding the PGF-2α-induced intracellular signal transduction pathway that ultimately results in exocytosis of luteal oxytocin. Evidence is also presented for potential autocrine/paracrine actions of oxytocin in regulating progesterone production by luteal and granulosa cells. Concluding remarks highlight aspects about luteal oxytocin production that require further research.